EFFECT OF MELATONIN ON NUCLEAR MATURATION OF CAPRINE OOCYTES - KUSHWAH, B S; KHARCHE, S D; AGARWAL, J; SIKARWAR, A K S; PATHAK, J; AGARWAL, S (The Indian Journal of Animal Reproduction, 2022)
Melatonin at the concentrations of 0, 5, 10, 20, 30, 40, and 50 ng/ml was used in maturation medium to assess the impact on in vitro maturation of caprine oocytes. The oocytes from slaughter house derived ovaries were subjected to in vitro maturation at 38.5°C with 5%CO2. After culture for 27h, over 90% COCs had full cumulus cell expansion. The degree of cumulus cell expansion remained similar (p>0.05) on increasing melatonin concentration, however, oocytes incubated in 30 and 50 ng/ml melatonin containing maturation media for 27 h, result in 80% and 18.9% nuclear maturation rate, respectively, which were different (p<0.05) from control (45.3%). The nuclear maturation rate decreased (p<0.05) when melatonin concentration was increased from 30 to 40 and 50 ng/ml (80% vs. 28.3% and 18.9%, respectively). In conclusion, melatonin improved nuclear maturation of caprine oocytes at 30 ng/ml, whereas a high concentration of melatonin may affect caprine oocytes meiotic maturation at metaphase-II stage and can be toxic for caprine oocytes.